Human Antibody Responses to the Polyclonal Dryvax Vaccine for Smallpox Prevention Can Be Distinguished from Responses to the Monoclonal Replacement Vaccine ACAM2000 - Pugh, Christine (American Society for Microbiology, 2014)
Dryvax (Wyeth Laboratories, Inc., Marietta, PA) is representative of the vaccinia virus preparations that were previously used for preventing smallpox. While Dryvax was highly effective, the national supply stocks were depleted, and there were manufacturing concerns regarding sterility and the clonal heterogeneity of the vaccine. ACAM2000 (Acambis, Inc./Sanofi-Pasteur Biologics Co., Cambridge, MA), a single-plaque-purified vaccinia virus derivative of Dryvax, recently replaced the polyclonal smallpox vaccine for use in the United States. A substantial amount of sequence heterogeneity exists within the polyclonal proteome of Dryvax, including proteins that are missing from ACAM2000. Reasoning that a detailed comparison of antibody responses to the polyclonal and monoclonal vaccines may be useful for identifying unique properties of each antibody response, we utilized a protein microarray comprised of approximately 94% of the vaccinia poxvirus proteome (245 proteins) to measure protein-specific antibody responses of 71 individuals receiving a single vaccination with ACAM2000 or Dryvax. We observed robust antibody responses to 21 poxvirus proteins in vaccinated individuals, including 11 proteins that distinguished Dryvax responses from ACAM2000. Analysis of protein sequences from Dryvax clones revealed amino acid level differences in these 11 antigenic proteins and suggested that sequence variation and clonal heterogeneity may contribute to the observed differences between Dryvax and ACAM2000 antibody responses.